RANCANG BANGUN SISTEM PENGENDALIAN LAJU PRODUKSI BROWN’S GAS BERBASIS MIKROKONTROLLER ATMEGA8535 - Siti Sofiya; Ya' Umar (Indonesian Journal of Fundamental Sciences, 2018)
This system was developed by controlling the production flowrate of brown gas by regulating the voltage that will enter the electrolysis process, so that the flowrate of HHO gas produced in accordance with the gas rotation on the motorcycle. This research uses ATmega8535 microcontroller as a controller and potentiometer 10K which has been connected with motor rotation / speed of motorcycle that serves to move the set point that has been programmed with microcontroller. The result of this research got control response through several set point. Set point 0.2 liter / min; 0.35 liters / min; 0.45 liters / min; 0.55 liters / min; 0.7 liters / min obtained each settling time of 100s, 280s, 300s, 260s, 300s and steady state errors each set point of 5%, 2.8%, 3.3%, 2.3% 4.8%